2015
DOI: 10.1016/j.labeco.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Do interventions targeted at micro-entrepreneurs and small and medium-sized firms create jobs? A systematic review of the evidence for low and middle income countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
95
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 46 publications
0
95
0
4
Order By: Relevance
“…Figure 3 shows that the evidence from 18 countries, most of which are in the Latin American region. As noted in Grimm and Paffhausen (2015), this could be because countries in this region have many experiences with active labor market policies over the past two decades. For firm performances, we grouped various outcomes such as profits, revenues, sales, added value, stock of assets, return on assets, gross production, and firm productivity (measured as total factor productivity).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 shows that the evidence from 18 countries, most of which are in the Latin American region. As noted in Grimm and Paffhausen (2015), this could be because countries in this region have many experiences with active labor market policies over the past two decades. For firm performances, we grouped various outcomes such as profits, revenues, sales, added value, stock of assets, return on assets, gross production, and firm productivity (measured as total factor productivity).…”
Section: Search Resultsmentioning
confidence: 99%
“…These businesses, especially in LMICs, comprise less productive or informal enterprises with only a few employees at the fringes of markets. This is a major difference in our review when compared to Grimm and Paffhausen (2015) who included studies focused on self-employed and microfinance. Further, these enterprises are often ineligible for the public interventions covered in this review.…”
Section: Inclusion Criteria and Search Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…As noted in Grimm and Paffhausen (2015), this could be because countries in this region have many experiences with active labor market policies over the past two decades. For firm performances, we grouped various outcomes such as profits, revenues, sales, added value, stock of assets, return on assets, gross production, and firm productivity (measured as total factor productivity).…”
Section: Figure 2 -Cumulative Number Of Studies Per Yearmentioning
confidence: 99%
“…We did not conduct moderator analysis by all types of global region, only for those regions where we had sufficient observations to undertake 15 Studies were done in different countries, different years, and scale as some used administrative data and other small-scale RCTs. 16 For instance, a paper by Grimm and Paffhausen (2015) studies a similar issue but focuses only on employment outcomes. Their search was done after 1990 and only one paper from prior to the year 2000 (Fretwell et al, 1999) was found.…”
Section: Study Limitationsmentioning
confidence: 99%